Are you prepared for mediation? - Zack, James (Acta Structilia, 2002)
This article discusses mediation as an alternative dispute resolution (ADR) process. It identifies why we ought to study the mediation process and discusses some of the good and bad points concerning the use of mediation as a form of dispute resolution. Finally, the article offers a number of suggestions as to how to prepare for and win at a mediation session.